James Green Stewart (1825-1881) - Coates, Ken (ARCTIC, 1986)
James Green Stewart, a classic example of the often-neglected second rank of the northern exploratory corps, made a noteworthy contribution to the opening of the far northwest. Although his part in northern exploration has been obscured by the more dynamic and public careers of his superior officers, most notably Robert Campbell, Stewart played a vital role in the Hudson's Bay Company's efforts to expand into the Yukon River valley. . Campbell had been active in the Liard and Pelly River regions for almost a decade and had just opened Fort Selkirk at the junction of the Pelly and Lewes (Yukon) rivers when Stewart joined him in 1848. As Campbell's assistant, Stewart faced the onerous task of helping to make this isolated fur post a viable enterprise. The challenge proved difficult and, ultimately, unsuccessful. Fort Selkirk was poorly positioned, for it thrust the Company's trade into the midst of trading networks maintained by the coastal Tlingit Indians, who, ironically, exchanged their furs at coastal points with other Hudson's Bay Company traders. The post suffered as well from its isolated position. Supplies had to be brought in along the Liard River, a violent and dangerous stream that claimed the lives of many Company tripmen. . in 1852, Campbell and Stewart were forced to abandon the post they had fought so hard to sustain, when Chilcat (Tlingit) Indians, long-time rivals of the Hudson's Bay Company traders at Fort Selkirk, attacked it. . for both Stewart and Campbell, the debacle at Fort Selkirk marked the end of their Yukon careers. Stewart, however, continued to serve in the North. He was stationed for short periods at Fort McPherson, Fort Carleton, and Fort Resolution. In 1855, Stewart was assigned to assist James Anderson's Back River expedition, sent to confirm reported sightings of the lost crew of John Franklin. The journey was wracked by discord between the two principal men. Anderson repeatedly overruled Stewart, challenging his selection of guides and route. Bad luck and poor planning plagued ...